A facile approach for rapid on-site screening of nicotine in natural tobacco. (April 2020) - Yu, Chaofan; Yu, Jie; Zhang, Huirong; He, Ziyan; Sha, Yunfei; Liu, Baizhan; Wang, Ying
Abstract: Nicotine (Nic) exposed to the environment which comes from tobacco products is the main addictive agent and specific classes of hazardous compound that merit concern. In this study, we have established a fast and reliable method to achieve specific detection of Nic in natural nicotiana tabacum within 30 s through a miniaturized platform based on screen printed gold electrode (SPE). A simple electrochemical pretreatment mean was employed on gold surface that led to the exposure of Au (111) facet and a convenient sample pretreatment method was adopted to realize the extraction of Nic in tobacco. The present electrochemical sensor exhibits an ample range of sensing from 10 μg/g to 200 μg/g, which is able to compliance with tobacco industry testing standards of actual samples. Over 60 sampling points from different origins in China or other countries were performed with direct analysis using this method and satisfactory results have been obtained. The proposed approach was demonstrated to be a very promising platform for significantly improving analytical efficiency in laboratories as well as for monitoring the source reduction control of Nic in the environment. Graphical abstract: Image 1 Highlights: E-pretreatment approach was carried out to the exposure of Au (111) facet. Rapid extraction of nicotine in tobacco was realized. Rapid on-site screening of nicotine in natural tobacco was achieved within 30s. Over 60 sampling points were successfully performed by this method.